2019
DOI: 10.1177/2396987319843701
|View full text |Cite
|
Sign up to set email alerts
|

Posterior circulation stroke diagnosis using HINTS in patients presenting with acute vestibular syndrome: A systematic review

Abstract: Acute vestibular syndrome-vertigo, nausea/vomiting, nystagmus and gait unsteadiness-is common, and differentiating posterior circulation stroke from a peripheral cause can be challenging. The National Institute of Health Stroke Scale (NIHSS) does not include acute vestibular syndrome, and early computed tomography scanning cannot rule out acute ischaemia. A positive Head Impulse-Nystagmus-Test of Skew (HINTS) test suggests posterior circulation stroke in acute vestibular syndrome when any of three signs are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 33 publications
(50 reference statements)
0
24
0
1
Order By: Relevance
“…CTB in detection of acute ischemic stroke is reported to be only 16% sensitive compared with other bedside battery of physical examinations such as HINTS, with reported sensitivity of 100% and specificity of 96% 15,16 . A systematic review concerning the screening for stroke with the bedside battery of examinations, reported a pooled sensitivity of 95.5% (95% CI 92.6–98.4%) and specificity of 71.2% (95% CI 67.0–75.4%) 17 . However, neither the HINTS assessment nor imaging provide any diagnostic value in the diagnosis of BPPV; where the bedside vestibular examination is normal aside from provocative manoeuvres and imaging is normal regardless of modalities.…”
Section: Discussionmentioning
confidence: 99%
“…CTB in detection of acute ischemic stroke is reported to be only 16% sensitive compared with other bedside battery of physical examinations such as HINTS, with reported sensitivity of 100% and specificity of 96% 15,16 . A systematic review concerning the screening for stroke with the bedside battery of examinations, reported a pooled sensitivity of 95.5% (95% CI 92.6–98.4%) and specificity of 71.2% (95% CI 67.0–75.4%) 17 . However, neither the HINTS assessment nor imaging provide any diagnostic value in the diagnosis of BPPV; where the bedside vestibular examination is normal aside from provocative manoeuvres and imaging is normal regardless of modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last years, algorithms have been suggested to distinguish between posterior circulation stroke and vestibular neuritis in AVS, i.e., in patients presenting with rotational vertigo, horizontal-rotatory spontaneous nystagmus, postural imbalance with directional falls, nausea, and vomiting. For clinical evaluation, the HINTS procedure (head impulse test, gaze evoked nystagmus, skew deviation) is now widely applied [11] but its usability is still under discussion [15,26]. In addition, there is growing evidence for predictive factors in non-AVS VD [35].…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] A meta-analysis examined the accuracy of positive HINTS in identifying PCS in acute vertigo patients and found it to be 95.5% (95% CI: 92.6–98.4%) sensitive and 71.2% (95% CI: 67.0–75.4%) specific. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%